Johnny Depp Starts Here - Pomerance, Murray, 1946- (Book collections on Project MUSE., 2005)
Rom beloved bad-boy to cool and captivating maverick, Johnny Depp has inspired media intrigue and has been the source of international acclaim since the early 1990s. He has attracted attention for his eccentric image, his accidental acting career, his beguiling good looks, and his quirky charm. In Johnny Depp Starts Here, film scholar Murray Pomerance explores our fascination with Depp, his riddling complexity, and his meaning for our culture. Moving beyond the actor's engaging and inscrutable private life, Pomerance focuses on his enigmatic screen performances from A Nightmare on Elm.